Kemampuan Daya Hambat Ekstrak Buah Pala (Myristica fragrans H.) Terhadap Candida albicans (Isolation and Analysis of Proteolytic Activity of Local Actinomycetes from Aceh, Indonesia) - Yulia Sari Ismail; Ainal Haniyati Ulfa; Isnaini Putri; Lenni Fitri (Jurnal Bioleuser, 2024)
The aim of this study were to determine the content of phytochemical compounds from tree parts of nutmeg (flesh, mace and seed),to compare the inhibitory effect of the extracts from the tree parts of the nutmeg (flesh, mace and seed) and the concentration that were effective in inhibiting the growth of the fungus Candida albicans. The extraction method was the maceration, the phytochemical testing was carried out qualitatively, and the antifungal activity was tested using punch hole method with concentrations of 25, 50, 75 and 100 %, positive control using ketoconazole and negative control using steril distilled water The result of this study showed that the etanol extract of nutmeg flesh was effective in inhibiting the growth of the fungus Candida albicans at concentration 75 % dan 100%. While the seed extract of nutmeg had a low inhibition zone. The etanol extract of nutmeg flesh and mace can be potential as antifungal.